2024
DOI: 10.1101/2024.02.06.578742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

αKG-mediated carnitine synthesis promotes homologous recombination via histone acetylation

Apoorva Uboveja,
Zhentai Huang,
Raquel Buj
et al.

Abstract: Homologous recombination (HR) deficiency enhances sensitivity to DNA damaging agents commonly used to treat cancer. In HR-proficient cancers, metabolic mechanisms driving response or resistance to DNA damaging agents remain unclear. Here we identified that depletion of alpha-ketoglutarate (αKG) sensitizes HR-proficient cells to DNA damaging agents by metabolic regulation of histone acetylation. αKG is required for the activity of αKG-dependent dioxygenases (αKGDDs), and prior work has shown that changes in αKG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…[24] Furthermore, we recently found that inhibition of wildtype IDH1 and depletion of αKG specifically inhibits HR-mediated DSB repair via a carnitine-mediated histone acetylation. [116] In CCNE1-driven models, this axis was necessary for resistance to DNA damaging agents such as cisplatin and olaparib.…”
Section: Isocitrate Dehydrogenasementioning
confidence: 99%
See 1 more Smart Citation
“…[24] Furthermore, we recently found that inhibition of wildtype IDH1 and depletion of αKG specifically inhibits HR-mediated DSB repair via a carnitine-mediated histone acetylation. [116] In CCNE1-driven models, this axis was necessary for resistance to DNA damaging agents such as cisplatin and olaparib.…”
Section: Isocitrate Dehydrogenasementioning
confidence: 99%
“…As we have discussed above, prior studies have interrogated a link between ACLY and both mutant and wildtype IDH1 and DNA repair. [24,110,116,156] However, many other TCA cycle enzymes and metabolites that affect the epigenome are also altered in ovarian cancer. As DNA repair genes such as BRCA1 are hypermethylated in ovarian cancer, this raises the intriguing question as to whether this can be modulating via metabolism.…”
Section: Future Perspectivesmentioning
confidence: 99%